PENINGKATAN KEMAMPUAN GURU DI KEGIATAN PEMBELAJARAN MEMBEDAKAN BERMACAM-MACAM RASA BAU DAN SUARA DENGAN PENDEKATAN SAINTIFIK KELOMPOK B TK NEGERI PEMBINA UJUNGBATU - Mariati Marzuki Yunus (JURNAL PENDIDIKAN ROKANIA, 2021)
The scientific learning process in kindergarten is the process of providing stimulation through scientific activities so that the growth and formation of children's brain networks will be networked with each other and more and more networks will be formed so that children progress in the development of their intelligence getting better from day to day. Observations on the ability of teachers in learning activities to distinguish various tastes, smells and sounds, with scientists in the TK B Negeri Pembina Ujungbatu, did not achieve the learning objectives that were not in accordance with what was planned in the RPPH. Therefore, the formulation of the problem from this research is how to improve the ability of teachers in learning activities to distinguish various tastes, smells, sounds, and scientifically in the TK B Negeri Pembina Ujungbatu. This School Action Research is qualitative using descriptive analysis consisting of 2 cycles. This study found that there was a significant increase in teacher competence in compiling and carrying out scientific activities according to the RPPH in achieving learning objectives.